Between consumption, accumulation and precarity: The psychic and affective practices of the female neoliberal spiritual subject - Carr, Melissa; Kelan, Elisabeth K (Human relations (New York), 2023)
Why do gig workers perceive work practices as aspirational in spite of their precarity? Selling beauty products through their networks appeals to many women as a convenient way to earn an income. Drawing on interviews and observations with women distributors of beauty products in a network marketing company, this article shows how aspirational messaging that appears spiritual is used to encourage these women to think and feel that they are in charge of their own destiny while making it difficult for those women to articulate the precarious conditions that are associated with such work. Practices that encourage those women to think in specific ways include internalising the right spiritual dispositions, developing as an entrepreneurial spiritual subject and selling the self. Women are also encouraged to feel in specific ways by monitoring how they feel about themselves and others. The article shows how ‘thinking rules’ and ‘feeling rules’ are used to construct an ideal female neoliberal spiritual subject in new forms of organising who is selling and consuming beauty products while aspirational-spiritual messaging makes it difficult to articulate precarity.